The Teaching Strategy in Reading Comprehension in Grade 2 Students of MtsN Serdang Bedagai - Khoiriyah Panjaitan; Hariyanto Hariyanto; Ahmad Laut Hasibuan (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2021)
This research was aimed to figure out the strategies used by English teachers in teaching reading and how they applied the strategies. It was designed as descriptive qualitative research. Participants of the research were two English teachers who taugh the 2 grade the students. Each English teacher had eight meetings observed by the researcher. The research instruments aere strategies checklist and interview. They were used to figure out the strategies used and how the English teachers applied the strategies in teaching reading comprehension. The result of the data were analyzed and broken down into three stages or Data Reduction, Data Display, and Drawing Conclusion or Interpretation. The previous studies showed that the teachers’ strategies were very effective in teaching reading comprehension. On the other hand, the use of too many strategies would affect students’ performances in learning reading comprehension. This reason was contradicted with the conducted the researcher in Junior High School Number 9 Bengkulu. This research showed that the teachers in applying strategies only use two or three strategies. Combination of some strategies was more appropriate comparemany strategies used by the teachers. The students would be more focused if the teacher used fewer strategies but well applied in teaching reading comprehension.